Circulating CD14+HLA-DR−/low Myeloid-Derived Suppressor Cells as Potential Biomarkers for the Identification of Psoriasis TCM Blood-Heat Syndrome and Blood-Stasis Syndrome. (15th April 2020) - Sun, Shipeng; Wei, Yali; Zeng, Xue; Yuan, Yuliang; Wang, Na; An, Cheng; Duan, Jinlong; Pang, Bo; Hong, Zifu; Liu, Guijian
Abstract : Psoriasis is a chronic autoimmune disease. Identification of the biomarkers responsible for Traditional Chinese Medicine (TCM) syndromes of psoriasis can help researchers recognize the different aspects of psoriasis and find novel therapeutic targets for the treatment of psoriasis. The current study investigated the levels of circulating Mo-MDSCs and Mo-MDSC-associated immune factors in the peripheral blood of psoriasis patients with different TCM syndromes. We found that the frequency of Mo-MDSCs (CD14 + HLA-DR −/low cells) among CD14 + cells from plaque psoriasis patients with blood-stasis (BS) syndrome was significantly increased when compared with healthy controls p < 0.001 and blood-heat (BH) syndrome group p < 0.001, respectively. However, serum IL-2, IL-4, IL-6, IL-10, IL-17A, TNF- α, IFN- γ, iNOS, Arg-1, and NO concentration showed no statistically significant difference between healthy controls and psoriasis patients as well as no significant difference between the BH and BS syndrome groups. Compared with healthy controls, the mRNA expression of Arg-1, TNF- α, ROR- γ, and PD-L1 was increased, while the mRNA expression of PD-1 and IL-10 was decreased in PBMCs from psoriasis patients. Moreover, the mRNA expression of TNF- α and FOXP3 in PBMCs showed a pronounced statistical difference between the psoriatic BH syndrome group and the BS syndrome group. Therefore, we provide evidence that the percentage of CD14 + HLA-DR −/low MDSC/ CD14 + cells and TNF- α and Foxp3 mRNA expression levels in PBMCs are potential biomarkers for distinguishing TCM BH syndrome and BS syndrome.